The Origin of Moral Norms in Business Ethics and Marketing Ethics: Personalism versus Utilitarianism - Adam Zadroga (Seminare, 2022)
The article focuses on the possibility of using the principles of personalism and utilitarianism in business ethics and marketing ethics. The author answers the question: Why should we first choose personalism, and not utilitarianism? The main thesis of this article is that for business ethics and marketing ethics the personalistic norm of morality is more appropriate than the utilitarian standard of morality. The article aims: (1) at assessing the utilitarian standard of morality used in business and marketing ethics; (2) at introducing the concept of business ethics and marketing ethics based on the assumptions of personalism